THE ROLE OF HUMAN CAPITAL IN MARRIED WOMEN'S LABOR MARKET PARTICIPATION: A MICRODATA ANALYSIS FROM SAKERNAS - Setyanti, Axellina Muara; Finuliyah, Firdaus (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
This study aims to analyze the effect of human capital on the tendency of married women to enter the labor market. With 149,508 samples from the National Labor Force Survey, this study uses a binary logistic regression analysis technique with several modifications to grouping samples based on rural – urban categories, and types of work. This study found that in general observation, the tendency to work increased in the group of women with higher education (diploma and university) although not significantly. The same thing was also found in both the rural and urban classifications. Furthermore, in the classification based on the type of work, only in the type of work employees/staff/laborers of secondary and higher education both increase the tendency to work. Women with higher education were found to be more likely to work after marriage, indicated by a higher odds ratio than women with secondary education. The same effect was not found in the type of work self-employed, casual workers, or family workers. The findings of this study imply that on average to the secondary level, education does not affect the participation of married women in the labor market in Indonesia, but only in higher education and formal employment.